pengaruh promosi dan literasi terhadap keputusan pembelian produk pegadaian syariah di Surabaya - Faransyah, Rifky; Prabowo, Prayudi Setiawan (Universitas Negeri Surabaya, 2020)
The Financial Services Authority conducted a national survey of the literacy level of Indonesian people as many as 8000 people from 20 provinces and produced only 14.85 percent which was well literate, while 38.89 percent was quite literate and 45.44 percent non-literate and the promotion rate was quite literate. conducted by sharia pawnshops that are considered less than optimal by the community through initial surveys conducted by researchers, therefore this study aims to determine the effect of promotion and literacy on purchasing decisions of Sharia pawnshops in Surabaya, both partially and simultaneously. The sample in this study were 100 respondents who were Sharia Pegadaian customers. This study uses multiple linear models to obtain answers to the research objectives. Where the results are obtained partially and simultaneously, there is a positive influence from the promotion and literacy variables on the purchasing decision variable. The results obtained from the R2 test, the independent variable has a simultaneous effect of 0.763 or 76.3% on the dependent variable. While there is a residual of 0.237 or 23.7% influenced by other factors outside the research variables